(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
Repo operations, short for repurchase operations, are financial transactions commonly used in the banking and financial sectors. They involve the sale of securities with an agreement to repurchase them at a later date. This article provides an overview of repo operations, their purpose, mechanics, and significance in the financial markets.